PENGARUH KECEPATAN PUTARAN TERHADAP KINERJA TERMAL ROTATING CLOSED THERMOSYPHON - Arif Rochman Fachrudin (INFO-TEKNIK, 2017)
Closed thermosyphon is a cooling device that allows the transfer of a certain amount of heat through a small surface area. Thermoshypon is a pipe consisting of 3 main parts: evaporator, adiabatik and condenser. The evaporator part is the part that receives heat and absorbs it to be brought to the condenser, which is the part that releases heat into the environment. The working process of closed thermosyphon is the fluid in the evaporator heated until it reaches the boiling point so it will evaporate to the condenser. In the condenser, heat is released with the help of a heat sink. From the fluid condenser back to the evaporator due to the force of gravity. This study aims to investigate the effect of rotational rotation speed on the performance of closed thermosyphon.           In this study, made of copper with a diameter of 9.52 mm and a total length of 400 mm. The evaporator region as the heat-affected side, the adiabatic portion is isolated so that there is no heat exchange with the environment and the condenser area is installed a heat sink which aims to remove heat from the closed thermosyphon into the environment. This research is done by varying the speed of rotation in thermosypon. The rotation variations used in this study are 100 rpm, 200 Rpm, 300 Rpm, 400 Rpm, 500 Rpm and 600 Rpm. The required data are temperature on evaporator (Te), condenser part temperature (Tk1, Tk2, Tk3) and air temperature (Tu).           The results showed that, Thermal resistance at the smallest Closed thermosyphon (0,50C / W) occurred at the speed of rotation 600 rpm with input power of 63 W. At the same rotation speed, the higher the input power, the greater the heat flux and power Output. The experimental process is the largest output power and the largest heat flux occurs at the highest input power, 63 W and the highest rotational speed, 600 rpm that produces 31 W output power and 26 W / Cm2 heat flux.